2021
DOI: 10.5152/dir.2020.20143
|View full text |Cite
|
Sign up to set email alerts
|

Managing occluded stents in biliary obstruction using radiofrequency ablation combined with 125I-strand brachytherapy

Abstract: elf-expandable metallic stent (SEMS) placement is an effective treatment for malignant biliary obstruction (1). However, stent restenosis occurs within 6 months in over 50% of patients, due to tumor ingrowth, overgrowth, epithelial hyperplasia, and biliary sludge formation (2, 3). There are no clear recommendations regarding how to reopen SEMS occlusions. Recently, some studies reported the safety and efficacy of a Habib EndoHPB percutaneous radiofrequency ablation (PRFA) catheter for re-opening occluded SEMSs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Moreover, 125 I brachytherapy can be completed at home, and reducing social costs. Other scholars have applied ILBT using 125 I strands to treat malignant biliary obstruction [ 13 , 14 ] and vascular thrombus [ 15 , 16 ], and showed that the local tumor response was better than that of single stenting, which was expected. Local 125 I brachytherapy inhibits the proliferation of intra-luminal tumors to some extent, resulting in long-term stent patency.…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, 125 I brachytherapy can be completed at home, and reducing social costs. Other scholars have applied ILBT using 125 I strands to treat malignant biliary obstruction [ 13 , 14 ] and vascular thrombus [ 15 , 16 ], and showed that the local tumor response was better than that of single stenting, which was expected. Local 125 I brachytherapy inhibits the proliferation of intra-luminal tumors to some extent, resulting in long-term stent patency.…”
Section: Discussionmentioning
confidence: 90%